The Hospitalist Model and Oncology: Oncologist Opinions About Inpatient Cancer Care Delivery. (18th August 2020) - Atlas, Kathleen R.; Egan, Barbara C.; Novak, Caroline J.; Sidlow, Robert
Abstract: Hospitalists, rather than oncologists, are increasingly providing inpatient medical care to hospitalized patients with cancer, yet the opinions of oncologists regarding this model of care delivery are unknown. A survey was conducted assessing these opinions and experiences with inpatient cancer care delivery at a tertiary cancer center. Only 30% of oncologists agreed that caring for hospitalized patients with cancer was an efficient use of their time, and most believed a hospitalist service allowed them to pursue other interests. Most had a positive experience with hospitalists, agreeing that hospitalists can diagnose and manage toxicities of cancer therapy, exhibit professionalism, and communicate with them and their patients appropriately. Hematologic malignancy specialists were more likely to value inpatient service time and had less confidence in the ability of hospitalists. Overall, the hospitalist model was generally accepted by oncologists and will continue to be an important part of oncologic care delivery. Abstract : The hospitalist model of inpatient care delivery is an accepted standard of care for hospitalized patients; however, the perceptions of oncologists about inpatient cancer care delivery and the hospitalist model are unknown. This study was conducted to understand the opinions of oncologists toward inpatient service duties and an oncology hospital medicine practice.